Chronic Jet Lag Simulation Decreases Hippocampal Neurogenesis and Enhances Depressive Behaviors and Cognitive Deficits in Adult Male Rats - Horsey, Emily A.; Maletta, Teresa; Turner, Holly; Cole, Chantel; Lehmann, Hugo; Fournier, Neil M. (Frontiers in Behavioral Neuroscience, 2020)
Abstract There is a long history that protracted periods of circadian disruption, such as through frequent transmeridian travel or by rotating shift work, can have a significant impact on health and brain function. In addition, several studies have shown that chronic periods of circadian misalignment can be a significant risk factor for the development of depression and anxiety in some individuals with a history of psychiatric illness. In animal models, circadian disruption can be introduced through either phase advances or delays in the light-dark cycle. However, the impact of chronic phase shifts on affective behaviour in rats has not been well studied. In the present study, male rats were subjected to either weekly 6 h phase advances (e.g., traveling eastbound from New York to Paris) or 6 h phase delays (e.g., traveling westbound from New York to Hawaii) in their light/dark cycle for 8 weeks. The effect of chronic phase shifts was then examined on a range of emotional and cognitive behaviours. We found that rats exposed to frequent phase advances, which mirror conditions of chronic jet lag in humans, exhibited impairments in object recognition memory and showed signature symptoms of depression, including anhedonia, increased anxiety behaviour, and higher levels of immobility in the forced swim test. In addition, rats housed on the phase advance schedule also had lower levels of hippocampal neurogenesis and immature neurons showed reduced dendritic complexity compared to controls. These behavioural and neurogenic changes were direction-specific and were not observed after frequent phase delays. Taken together, these findings support the view that circadian disruption through chronic jet lag exposure can suppress hippocampal neurogenesis, which can have a significant impact on memory and mood-related behaviours.